People’s Cognitive Beliefs and Definitions About Homosexuality - Spahiu, Desarta (European Scientific Journal, ESJ, 2017)
This study aims to explore and analyze the process of defining homosexuality as an act of political implications. Defining the homosexuality influence the terms of social and political debate and implies distinct lines of actions. Qualitative analysis of the individual interviews used in this study shows how people discursively construct opinions about homosexuality. This study includes 10 participants using in-depth interviews and literature review as a research method. Evidence of this study indicates that cognitive beliefs and definitions about homosexuality are related directly and indirectly on attributions of causes that are biological or lifestyle choices in discourses. Surprisingly there is a significant number of responses about homosexuality that are not clearly defined. For some people, homosexuality can purport multiple things and others don’t think that they have the knowledge to give an opinion about the reasons that causes the homosexuality. In order to generate statistical estimates about how prevalent these different patterns of discourse are in the population in large, we must generate survey instruments that are more capable of measuring the complexity of people’s understandings of homosexuality.